A critique of the "ultra‐high risk" and "transition" paradigm. Issue 2 (June 2017) - van Os, Jim; Guloksuz, Sinan
Abstract : The transdiagnostic expression of psychotic experiences in common mental disorder (anxiety/depression/substance use disorder) is associated with a poorer prognosis, and a small minority of people may indeed develop a clinical picture that meets criteria for schizophrenia. However, it appears neither useful nor valid to observe early states of multidimensional psychopathology in young people through the "schizo"‐prism, and apply misleadingly simple, unnecessary and inefficient binary concepts of "risk" and "transition". A review of the "ultra‐high risk" (UHR) or "clinical high risk" (CHR) literature indicates that UHR/CHR samples are highly heterogeneous and represent individuals diagnosed with common mental disorder (anxiety/depression/substance use disorder) and a degree of psychotic experiences. Epidemiological research has shown that psychotic experiences are a (possibly non‐causal) marker of the severity of multidimensional psychopathology, driving poor outcome, yet notions of "risk" and "transition" in UHR/CHR research are restrictively defined on the basis of positive psychotic phenomena alone, ignoring how baseline differences in multidimensional psychopathology may differentially impact course and outcome. The concepts of "risk" and "transition" in UHR/CHR research are measured on the same dimensional scale, yet are used to produce artificial diagnostic shifts. In fact, "transition" in UHR/CHR research occurs mainly as a function of variable sample enrichment strategies rather than the UHR/CHR "criteria" themselves. Furthermore, transition rates in UHR/CHR research are inflated as they do not exclude false positives associated with the natural fluctuation of dimensional expression of psychosis. Biological associations with "transition" thus likely represent false positive findings, as was the initial claim of strong effects of omega‐3 polyunsatured fatty acids in UHR samples. A large body of UHR/CHR intervention research has focused on the questionable outcome of "transition", which shows lack of correlation with functional outcome. It may be more productive to consider the full range of person‐specific psychopathology in all young individuals who seek help for mental health problems, instead of "policing" youngsters for the transdiagnostic dimension of psychosis. Instead of the relatively inefficient medical high‐risk approach, a public health perspective, focusing on improved access to a low‐stigma, high‐hope, small scale and youth‐specific environment with acceptable language and interventions may represent a more useful and efficient strategy.